Effect of Parenting Style, attachment to parents and self-compassion on the occurrence and recovery motivation for non-suicidal self-injury in adolescents - Liu, Pei; Liu, Jianbo; Li, Yi; Lu, Jianping (Frontiers in Psychology, 2024)
We would like to submit the original article entitled "Effect of Parenting Style, Attachment to Parents, and Self-compassion on the Occurrence and Recovery Motivation for Non-suicidal Self-injury in Adolescents", which we wish to be considered for publication in Frontiers of psychology. Nonsuicidal self injury in adolescents is a worldwide prevalent phenomena, factors that increase the motivation to recovery is important for adolescents and clinicians. This study aims to explore the effect of parenting styles, attachment to parents, and levels of self-compassion on the occurrence of non-suicidal self-injury (NSSI) behavior in adolescents, as well as investigating whether these factors influence the recovery motivation of adolescents engaging in NSSI.Frontiers in psychology is a peer-reviewed, open access journal that welcomes articles on a broad range of topics related to psychology, human behavior, and the mind.Pediatric Psychology section published empirical and theoretical research that has indirect or direct critical translational value for clinical practice in psychological childcare settings. We hope our manuscript is suitable for Frontiers in psychology We declare that this manuscript is being submitted to Frontiers in psychology alone at that point in time and has not been published anywhere, simultaneously